The effect of zirconia dipping time frequencies with different nanoparticles suspension on the micro-shear bond strength of zirconia to resin cement - Amory, Zainab S; Rashid, Mohammed; Saeed, Musab H (Journal of Baghdad College of Dentistry, 2025)
Background: Zirconia restoration attracted great attention because of its high mechanical and esthetic properties that meet the requirements of anterior and posterior restoration. This study aimed to evaluate the micro-shear bond strength between resin cement and zirconia surfaces coated with different nanooxides with different dipping time frequencies. Materials and Methods: HT Zirconia blocks (n=55) were divided into 5 groups according to the coating suspensions and the frequency of dipping times. Group A: dip in 50% SiO2+50%ZrO2 for 1min in frequency 4 times, group B: dipping in 50% SiO2+50% ZrO2 for 4min in frequency of 1 time, group C: dipping in 50% SiO2+50%Al2O3 for 1min in frequency of 4 times group D: dipping in 50%SiO2+50%Al2O3 for 4min in frequency of 1 times, group E: nontreated zirconia (control group). The coated surfaces were characterised using Field Emission Scanning Electron Microscopy (FESEM), X-ray diffraction (XRD), Energy Dispersive Spectroscopy (EDS), and atomic force microscopy (AFM). Resin cylinders were cemented onto the treated zirconia surfaces, and micro shear bond strength testing was performed. One-way ANOVA and Tukey’s post hoc test analyzed differences in bond strength between groups (p<0.05). Results: FESEM showed nanosilica-nano-zirconia coatings full coverage with porosity within the coating, and nanosilica-nano-alumina shows full coverage with crosslinking of the silica-alumina on the surface of Zirconia with creating a high ratio of porosity within the coating. XRD detected only a tetragonal phase in coated and nontreated zirconia, indicating no phase transformation in the coated zirconia surface by the dipping technique. The microshear bond strength was higher for all coating groups versus controls (p<0.05). Conclusion: The dip coating with the nanoparticle suspension consists of 50%SiO2+50%Al2O3 with a dip frequency of 1min for 4 times better than continuous dipping